The interdisciplinary team in type 2 diabetes management: Challenges and best practice solutions from real-world scenarios - McGill, Margaret (J Clin Transl Endocrinol, 2016)
The Global Partnership for Effective Diabetes Management has previously recommended the implementation of an interdisciplinary team (IDT) approach to type 2 diabetes (T2DM) management as one of 10 practical steps for health care professionals to help more people achieve their glycaemic goal. This article discusses some of the key contributors to success and also the challenges faced when applying IDT care, by examining case studies and examples from around the world. The real-world practices discussed show that implementing successful interdisciplinary care in diabetes is possible despite significant barriers such as established hierarchal structures and financial resource constraints. Instituting collaborative, integrated working relationships among multiple disciplines under strong leadership, together with enhanced and active communication and improved patient access to appropriate specialties is essential. Patients have a crucial role in the management of their own disease and including them as part of the treatment team is also critical. IDTs in diabetes care improve patient outcomes in terms of control of glycaemia and cardiometabolic risk factors, and decreased risk of diabetes complications. Ensuring access to an appropriate IDT, in whatever form, is paramount to enable the best care to be delivered.